2016
DOI: 10.3382/ps/pew233
|View full text |Cite
|
Sign up to set email alerts
|

Effect of long-term selection for egg production on eggshell quality of Japanese quail (Coturnix japonica)

Abstract: An experiment was conducted to evaluate egg quality and ultrastuctural measurements of eggshell using a Scanning Electron Microscope (SEM) in 2 lines (selected and control) of Japanese quail. A selection program was applied over 22 consecutive generations for higher egg production and lower broken egg percentage. The results revealed that the females of the selected line produced significantly (P < 0.01) higher egg mass compared to that of the control line. Also, the selection procedure significantly improved … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 20 publications
1
12
0
Order By: Relevance
“…Descriptive statistics for the external and internal egg quality traits are presented in Table 1. These findings are within the ranges for Japanese quail reported by Taha (2009), who found EN ranged from 51.97 to 72.83, and Fathi et al (2016), who observed average ENs of 57.0 and 65.8 eggs in the control and selected lines, respectively. The present study revealed that the average EW was 13.63 g. Khaldari et al (2010) and Copur et al (2010) reported similar averages of 13.40 g and 13.25 g. In contrast, lower EW with a range of 10.27 -12.76 g was reported for quails by Hassan et al (2003), Kul and Seker (2004), Sari et al (2016), Al-Daraji et al (2010), andNarinc et al (2015).…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…Descriptive statistics for the external and internal egg quality traits are presented in Table 1. These findings are within the ranges for Japanese quail reported by Taha (2009), who found EN ranged from 51.97 to 72.83, and Fathi et al (2016), who observed average ENs of 57.0 and 65.8 eggs in the control and selected lines, respectively. The present study revealed that the average EW was 13.63 g. Khaldari et al (2010) and Copur et al (2010) reported similar averages of 13.40 g and 13.25 g. In contrast, lower EW with a range of 10.27 -12.76 g was reported for quails by Hassan et al (2003), Kul and Seker (2004), Sari et al (2016), Al-Daraji et al (2010), andNarinc et al (2015).…”
Section: Resultssupporting
confidence: 90%
“…Round eggs and unusually long eggs do not look 'right', and do not fit well in egg cartons. These eggs are much more likely to be broken during shipment than those of normal shape, resulting in economic losses for breeders and traders (Uluocak, 1995;Fathi et al, 2016). Eggs that look abnormal are more likely to be rejected by the consumer, whereas defects in eggshell ultrastructure can result in breakage or impaired development of the embryo during incubation (Mills et al, 1994;Roberts, 2004;Duman et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A total of 460 eggs (230 eggs from each variety) were collected at 16 weeks of age. External and internal egg quality measurements were assessed according to Fathi et al [8]. Each egg was weighed to the nearest 0.1 g. Egg width (equatorial axis) and egg length (longitudinal axis) were measured using Vernier caliper to 0.1 mm.…”
Section: Methodsmentioning
confidence: 99%
“…These palisade layers are the columnar shape with the spongy structure. The narrow columnar shape provides high strength against breakage to the eggshell and shell thickness ( Ahmed et al, 2005 ; Fathi et al, 2016 ). The cuticle is the last layer to be deposited on the shell before egg laying.…”
Section: Introductionmentioning
confidence: 99%